The Assistance of Educational Props Development for Primary School and Early Childhood Education Teachers in Pekanbaru - Mujtahid, Iqbal Miftakhul; Berlian, Mery; Vebrianto, Rian; Thahir, Musa (International Journal of Elementary Education, 2021)
Community Service Program is done based on problems encountered by Primary School and Early Childhood Education Teachers in Riau Municipality and Province. Therefore, in order to maintain the sustainability of science education through practicum/experiment, then simple Educational Props alternative of Natural Sciences needs to be developed whose provision is easier and affordable and utilization is simple because it is not easily broken. Based on several problems identified, then solution that would be formulated was counselling and assistance in making educational props such as making educational props from secondhand goods, environment, and kahoot application as interesting memorable learning media for Primary School and Early Childhood Education Teachers in Pekanbaru. The service activities was Participatory Action Research (PAR) that was conducted through descriptive approach method. Based on the result of the activities, it can be considered as successfully overcoming the problem proven by the high teachers’ participation in participating in the training and the successfulness of the teachers in developing the educational props.